3D Tactical Floor Game Application for Visualization of Battle Operation Plan by Utilizing Three Act-Structure - Rickman Roedavan; Bambang Pudjoatmodjo; Sazilah Salam; Khaniza Nurussyifa (IJAIT (International Journal of Applied Information Technology), 2022)
Tactical Floor Game (TFG) is an activity to simulate tactics and test the concept of battle operation plans. The main focus in TFG activity is aligning planning logic with field execution estimates using storytelling, mainly through role-playing in a replica of the combat situation. TFG activity is usually done manually by laying out a paper map on the floor and pairing miniatures representing units in operation. In the digital version, TFG activity is typically presented in the form of short film segments representing a stage of combat preparation or by utilizing simple PowerPoint-based animations. The use of such multimedia is considered less representative and may not provide a realistic visualization in the context of battle simulations. This research aims to address the issue of creating realistic visualization and dynamic simulation in combat planning by developing an interactive multimedia application. The contribution to the field of knowledge in this research is focused on the application of the Three-Act Structure, a storytelling framework commonly used in films, into the process of developing multimedia applications. The test results indicate that an interactive multimedia application developed specifically for TFG activities can serve as a comprehensive visualization tool for testing the concept of battle operation plans.